Conflicts Over Locally Unwanted Land Uses (lulus): Reasons and Solutions for Case Studies in Izmir (turkey) - Atay Kaya, İlgi; Kaya Erol, Nursen; Kaya Erol, Nursen (Elsevier Ltd., 2016)
Land use planning affects many different and usually conflicting interests. While every land use planning decision has a potential of creating conflicts, Locally Unwanted Land Uses (LULUs) are the most conflict facing subjects in urban land use planning processes. This paper aims to answer the question “what are the reasons and solutions for conflicts in the planning processes of LULUs”. This paper is based on a research examining LULU cases in İzmir, Turkey including solid waste facilities, fisheries and quarries to find out the reasons and the solutions for LULU conflicts. The research findings suggest that the conflicts stem not only from negative effects of LULUs on environment and community but also from procedural deficiencies such as lack of knowledge and lack of trust. The findings also call for planning processes with more consideration of local level and public participation seeking for consensus. Meanwhile, the conclusions underline the limitations for the success of participatory processes in which conflicts are resolved with attempts including symbolic benefits rather than considering exact interests of local people. © 2016 Elsevier Ltd
Keywords: Conflict resolution; Fisheries; Land use planning; Locally Unwanted Land Uses; Solid waste facilities; Quarries